PENGARUH PEMBERIAN KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP LOYALITAS KARYAWAN PADA PT. BESMINDO ANDALAS SEMESTA DURI - Oktavianus, Davit; Karneli, Okta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to determine the effect of compensation and work environment on employee loyalty at PT.Besmindo Andalas Semesta Duri. The independent variables are compensation (X1) and work environment (X2). While the dependent variable is employee loyalty (Y). In this research, the method used is descriptive quantitative analysis with SPSS 24.0 program. The population in this study were permanent employees totaling 65 people, with the sample technique used, namely census/total sampling. Data collection techniques through questionnaires and interviews, types and sources of data using primary data and secondary data, measurement collection techniques using a Likert scale. From the data analysis which includes validity test, reliability test, simple linear regression analysis, multiple linear analysis, determination analysis and significance test with t test (partial) test, and f test (simultaneous). The results of this study indicate that the results of testing the first t test hypothesis, giving compensation to employee loyalty, namely t count (5,064) > t table (1,669) meaning that the effect of compensation has a significant effect on employee loyalty. The two work environments on employee loyalty are t count (8,469) > t table (1,669) meaning that the work environment has a significant effect on employee loyalty. The results of the f test of compensation and work environment have a significant effect on employee loyalty, namely f count (31,645) > (3.15) meaning that the provision of compensation and the work environment simultaneously has a significant effect on employee loyalty. Keywords: Compensation, Work Environtment, Employee Loyality